Metamorphic Inheritance, Lower‐Crustal Earthquakes, and Continental Rifting - Å. Fagereng; J. F. A. Diener; C. J. Tulley; B. Manda (Geochemistry, Geophysics, Geosystems, 2024)
Abstract The Malawi Rift is localized within Precambrian amphibolite‐granulite facies metamorphic belts, bounded by up to 150 km long border faults, and generates earthquakes throughout ∼40 km thick crust. Rift‐related faults are inferred to exploit pre‐existing weaknesses that allow rifting of otherwise dry and strong crust. It is unclear what these weaknesses are, and how localization into weak zones can be reconciled with strength required for lower crustal seismicity. We present results of mineral equilibria modeling, which indicate that Proterozoic metamorphism generated dry crust dominated by a quartz‐feldspar assemblage that is metastable at current conditions. For rift propagation to be possible at current cool thermal gradients and in mechanically strong, dry quartzofeldspathic rocks, mid‐ to lower‐crustal strain must be localized into relatively weak, inherited shear zones that deform primarily by aseismic, viscous creep. These shear zones are embedded within high‐strength crust, and interaction between creeping shear zones and enveloped or surrounding rocks may locally increase stress and trigger frictional, seismic slip at mid‐ to lower‐crustal depths. Over time, this interaction may produce a fracture network that allows infiltration of fluids. We therefore suggest that during rifting of previously deformed and metamorphosed crust, major faults are most likely to grow from below, with their location and orientation prescribed by underlying inherited viscous shear zones. In this case, fluids may infiltrate and locally weaken metastable lower crust, including allowing time‐dependent fluid‐driven seismicity and local partial melting, but length‐scales of this weakening is limited by the scale of the permeability network.